IN VITRO ANTIFUNGAL ACTIVITIES OF ESSENTIAL OIL PIMENTA RACEMOSA AGAINST FUNGAL ISOLATES FROM WAGASHI, A TRADITIONAL CHEESE PRODUCED IN BENIN - SESSOU, PHILIPPE; FAROUGOU, SOUAÏBOU; AZOKPOTA, PAULIN; YEHOUENOU, BONIFACE B.; YOUSSAO ABDOU KARIM, ISSAKA; SOHOUNHLOUE, KOKO CODJO DOMINIQUE (My University, 2014)
Traditional cheese wagashi, an important source of protein, is produced and preserved using rudimentary methods under unsanitary conditions. This fact may lead to wagashi contamination by spoilage and pathogenic strains especially fungi which may contribute to the loss of its quality and safety. A better control measure to prevent wagashi contamination by mycoflora and minimize public health hazards is necessary